Recent developments in heterogeneous photocatalytic water treatment using visible light-responsive photocatalysts: a review. Issue 19 (30th January 2015) - Dong, Shuying; Feng, Jinglan; Fan, Maohong; Pi, Yunqing; Hu, Limin; Han, Xiao; Liu, Menglin; Sun, Jingyu; Sun, Jianhui
Abstract : This review summarizes the recent progress in the design, fabrication, and application of visible light-responsive photocatalysts. Abstract : Visible light-responsive photocatalytic technology holds great potential in water treatment to enhance purification efficiency, as well as to augment water supply through the safe usage of unconventional water sources. This review summarizes the recent progress in the design and fabrication of visible light-responsive photocatalysts via various synthetic strategies, including the modification of traditional photocatalysts by doping, dye sensitization, or by forming a heterostructure, coupled with π-conjugated architecture, as well as the great efforts made within the exploration of novel visible light-responsive photocatalysts. Background information on the fundamentals of heterogeneous photocatalysis, the pathways of visible light-responsive photocatalysis, and the unique features of visible light-responsive photocatalysts are presented. The photocatalytic properties of the resulting visible light-responsive photocatalysts are also covered in relation to the water treatment, i.e., regarding the photocatalytic degradation of organic compounds and inorganic pollutants, as well as photocatalytic disinfection. Finally, this review concludes with a summary and perspectives on the current challenges faced and new directions in this emerging area of research.